Effect of drifts and currents on the validity of a fluid model for the atoms in the plasma edge. (October 2022) - Van Uytven, Wim; Dekeyser, Wouter; Blommaert, Maarten; Horsten, Niels; Baelmans, Martine
Abstract: The performance of advanced fluid neutral models for the simulation of deuterium atoms in the plasma edge of magnetically confined fusion devices is tested for the first time on cases that include drifts and currents in the plasma model, on a simplified Alcator C-mod case. The unadapted advanced fluid neutral model already gives quantitative agreement, with 5–30% fluid-kinetic discrepancy in the broad vicinity of the strikepoint. A new advective perpendicular transport term is proposed, which further reduces the fluid-kinetic discrepancies for cases with drifts. It is also shown that the ion-neutral current can be calculated consistently for fluid or kinetic neutrals, at least when only atoms are considered. However, its effect on the solution is very small for the studied case. Highlights: Simplified Alcator C-mod case with drifts. Assessment of advanced fluid neutral models. Drift-compatibility of fluid neutral models. Compare fluid neutrals with EIRENE in SOLPS-ITER. Comparison of ion-neutral current.